Staying grounded. (July 2021) - Foote, Peter; Gehring, Brian; Tucker, Colin
Abstract : In response to James McKenzie's Transactions article "Grounds for optimism" (March p27) and his 1 April appearance on the Physics World Weekly podcast, in which he discusses the clean-energy potential of heat pumps that warm homes with heat extracted from the ground.